Moderating effect of administrative role in the relationship between the SERVQUAL dimensions and Quality Service Provisions of local government in Dhaka City - Ashraf, Musfiq; Moniruzzaman, Md.; Quddus, S. M. Abdul (Academic Research Publishing Group, 2018)
The present study aims at investigating the moderating effect of administrative role in the relationships between the service quality dimensions, logistic support and perceived quality service of local government (Dhaka City Corporation) in the context of Bangladesh. For the purpose of the study, data were collected from 222 slum dwellers of Dhaka City living in the six big slums which are Shampur, Tejgaon, Bhasantak, Korail, Kamalapur and Zurain slums to examine the moderating effect. The responses were gathered with 5 point Likert scale with response options ranging from strongly agree (5) to strongly disagree (1) through a structured questionnaire survey. Collected data were analyzed using partial least square structural equation modeling technique (PLS-SEM) with the support of the software Smart PLS 2.0 M3. The findings reveal that administrative role positively moderates the relationship between assurance dimension and perceived service quality of local government; logistic support and perceived quality service and finally, the findings reveal that administrative role has significant moderating effect in the relationship between responsiveness and perceived service equality of local government. Hence, the findings give an indication that local government should play positive administrative role to improve the services quality and make their services effective for slum dwellers. The policy makers, local government and other related stakeholders might find this study as an essential tool in designing, developing and implementing their activities directed to the slum dwellers.